Spatial allocation without spatial recruitment in bumblebees. (28th January 2021) - Incorvaia, Darren C; Hintze, Arend; Dyer, Fred C
Abstract: Any foraging animal is expected to allocate its efforts among resource patches that vary in quality across time and space. For social insects, this problem is shifted to the colony level: the task of allocating foraging workers to the best patches currently available. To deal with this task, honeybees rely upon differential recruitment via the dance language, while some ants use differential recruitment on odor trails. Bumblebees, close relatives of honeybees, should also benefit from optimizing spatial allocation but lack any targeted recruitment system. How bumblebees solve this problem is thus of immense interest to evolutionary biologists studying collective behavior. It has been thought that bumblebees could solve the spatial allocation problem by relying on the summed individual decisions of foragers, who occasionally sample and shift to alternative resources. We use field experiments to test the hypothesis that bumblebees augment individual exploration with social information. Specifically, we provide behavioral evidence that, when higher-concentration sucrose arrives at the nest, employed foragers abandon their patches to begin searching for the better option; they are more likely to accept novel resources if they match the quality of the sucrose solution experienced in the nest. We explored this strategy further by building an agent-based model of bumblebee foraging. This model supports the hypothesis that using social information to inform search decisions is advantageous over individual search alone. Our results show that bumblebees use a collective foraging strategy built on social modulation of individual decisions, providing further insight into the evolution of collective behavior. Abstract : Animal groups, such as social insect colonies, must collectively gather enough resources to meet their energetic demands. Bumblebees may use social information from the nest to guide them to the best available resources. We present evidence showing that social cues from the nest can be used by bumblebees to trigger a search, speeding up the colony's allocation of foragers to the best available resources. These results allow us to better understand the evolution of collective foraging strategies.